New Materialism, Ethnography, and Socially Engaged Practice: Space-Time Folds and the Agency of Matter (Praxis Educativa, 2021)
This article is an investigation of the agency of matter and an exposition of the new materialist methods I have been developing as part of a muti-sited trans-national ethnography that features socially engaged arts practices alongside more traditional ethnographic and qualitative techniques. I think through the agency of matter and consider the temporality of matter as part of its agency, understanding these agents as constitutive features of the research assemblage. Drawing on ethnographic fieldwork from the United Kingdom, I examine how matter’s space-time can impact processes of making the social. I develop theoretical resources for moving the field forward. s
Keywords: ethnographies; methodologies; arts-based inquiry; methods of inquiry; feminist methodologies; new methods and methodologie